High-Dose Tigecycline in Elderly Patients with Pneumonia Due to Multidrug-Resistant Acinetobacter baumannii in Intensive Care Unit - Bai, Xiang-Rong (Infect Drug Resist, 2020)
PURPOSE: The association between clinical and microbiological outcomes and high-dose tigecycline (TGC) was assessed in elderly (≥60 years old) patients with hospital-acquired and ventilator-associated pneumonia due to multidrug-resistant Acinetobacterbaumannii(A. baumannii). This study also assessed tigecycline combination with different antibiotics and its influence on the outcome. PATIENTS AND METHODS: An observational retrospective cohort study was conducted. Patients over 60 years old were treated with standard-dose (SD) TGC (100-mg intravenous TGC initially, followed by 50-mg doses administered intravenously twice daily) and high-dose (HD) TGC (200-mg intravenous TGC initially, followed by 100-mg doses administered intravenously twice daily) for a microbially confirmed infection. The outcome was 30-day crude mortality, co-administered antimicrobial agent and the microbial eradication percentage in both groups. RESULTS: A total of 48 multidrug-resistant A. baumannii respiratory patients were identified. Tigecycline was administered to 85% of ventilation-associated pneumonia (VAP) patients (28/33) in the SD group and 80% of VAP patients (12/15) in the HD group. Combined therapy was the major treatment option in both groups, accounting for 85% and 87%, respectively. Median treatment duration in both groups was 7.36 vs 8.6 days, respectively. Survival days were 13.61 vs 12.4 days (P=0.357), respectively. The 30-day crude mortality was 39.4% (13/33) for the SD group and 14% (2/15) for the HD group (P=0.098). The microbial eradication rate of respiratory specimens in the SD group was higher than that in the HD group (P=0.02). The variables associated with 30-day crude mortality were chronic obstructive pulmonary disease (hazard ratio [HR] 11.63, 95% CI 1.094–123.058; P=0.042), tigecycline treatment duration (HR 0.690, 95% CI 0.515–0.926; P=0.013), and surgery before infection (HR 79.276, 95% CI 6.983–899.979; P=0.000). High-dose tigecycline was not associated with 30-day crude mortality (adjusted HR 0.329, 95% CI 0.074–1.460; P=0.145). Combined antibiotics was also not different between the two groups. CONCLUSIONS: High-dose tigecycline was not associated with 30-day crude mortality in elderly patients with pneumonia due to multidrug-resistant A. baumannii, although the microbial eradication rate was high.